2016
DOI: 10.1016/j.msec.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

In-situ photocrosslinkable nanohybrid elastomer based on polybutadiene/polyhedral oligomeric silsesquioxane

Abstract: Hydroxyl functionalized nano-sized POSS or ethyleneglycol as diol monomers was incorporated to hydroxyl-terminated polybutadiene (HTPBD) chain in the presence of fumaryl chloride as extender. Blue light photocrosslinking system based on camphorquinone (photoinitiator) and dimethylaminoethyl methacrylate (accelerator) was applied to cure these two synthesized fumarate based macromers. Self-crosslinkability of unsaturated macromers and also crosslinking in presence of a reactive diluent were investigated in abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…A sol fraction extraction study was performed on the reactive blended specimens using a procedure at references . At least 3 rectangular specimens for each composition were accurately weighed (W 1 ) and placed into 50 mL of toluene under gentle shacking at room temperature to swell and extract the unreacted PS and rubbers.…”
Section: Methodsmentioning
confidence: 46%
See 2 more Smart Citations
“…A sol fraction extraction study was performed on the reactive blended specimens using a procedure at references . At least 3 rectangular specimens for each composition were accurately weighed (W 1 ) and placed into 50 mL of toluene under gentle shacking at room temperature to swell and extract the unreacted PS and rubbers.…”
Section: Methodsmentioning
confidence: 46%
“…A sol fraction extraction study was performed on the reactive blended specimens using a procedure at references. 1,25,26 At least 3 rectangular…”
Section: Gel Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the inherent strength and rigidity of the inorganic POSS siliceous nucleus as well as the springiness of organic side substituents (R) can improve the overall performance of POSS/polymer nanohybrid matrices. In these nanohybrid materials, well‐dispersed POSS nanoparticles can enhance the morphological, mechanical, thermal, oxidative and biostability properties of hybrid polymers under critical situations …”
Section: Introductionmentioning
confidence: 99%
“…Other reactive compatibilizers used in PLA blends, promote exchange reactions between PLA's end functional groups (ie, hydroxyl or carboxyl) and the complementary groups in the compatibilizer. [7][8][9][10][11][12][13] In this research, reactive modification of PLA by PC and nanosilica particles is targeted. To this end, two different kinds of catalysts, dicumyl peroxide (DCP, a radical initiator) and Cobalt(II) acetylacetonate (a coordination catalyst), were employed to assist chemical grafting and transesterification reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%